Developing countries in the WTO legal system - Thomas, Chantal, 1971-; Trachtman, Joel P. (New York ; Oxford : Oxford University Press, 2009)
With contributions from some of the leading experts in international trade, law, and economics, Joel P. Trachtman and Chantal Thomas have compiled a comprehensive volume that looks at the positioning of developing countries within the WTO system.
Description based on print version record.
Includes bibliographical references and index.
Keywords: World Trade Organization -- Developing countries; Foreign trade regulation -- Developing countries; Free trade -- Developing countries; Tariff -- Law and legislation -- Developing countries; General Agreement on Tariffs and Trade (Organization); Developing countries -- Commercial policy